PERBANDINGAN HASIL REKAMAN EKG MENGGUNAKAN SADAPAN PREKORDIAL ECG SAFONE DAN SADAPAN PREKORDIAL EKG STANDAR - Yurike Reza; Wan Nishfa Dewi; Yulia Rizka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Background: Proper treatment is needed to reduce the mortality of cardiovascular diseases including ECG skills such as the accuracy of placing the precordial electrodes. ECG SafOne innovation was designed to help nurses to locate the precordial electrodes quickly and precisely. Purpose: The aim of this study is to compare ECG recording results between precordial leads ECG SafOne and ECG standard. Methods: This study used a quasi-experiment design with a one-group posttest-only design. The number of samples involved was 30 people who were selected using the purposive sampling technique. ECG recording was collected using both ECG SafOne and ECG standard and was observed using an observation sheet. This study used descriptive and Wilcoxon tests for data analysis. Results: The results of this study showed that more than half of the respondents were in the age range 46-65 years old (66,7%) and the majority of them were male (60%). Most respondents were diagnosed with Coronary Artery Disease with an average illness of about 7 years. In addition, the results of bivariate analysis depicted that there is no significant difference in the ECG recording results between precordial lead ECG SafOne and precordial lead ECG standard with (p values 1,00 > alpha 0.005). Conclusion: ECG recording results using ECG SafOne had shown similar results when compares to ECG standard. Suggestion: ECG SafOne can be used by healthcare professionals to perform ECG recording and further research is required to certain the sustainability and compatibility of ECG SafOne from the perspective of users.Key words: Electrocardiography, ECG recordings, precordial lead, ECG SafOne